2007
DOI: 10.1189/jlb.1206718
|View full text |Cite
|
Sign up to set email alerts
|

NKT cells direct monocytes into a DC differentiation pathway

Abstract: Monocytes can differentiate into macrophages or dendritic cells (DCs). The processes that promote their differentiation along one pathway rather than the other remain unknown. NKT cells are regulatory T cells that respond functionally to self and foreign antigens presented by CD1d molecules. Hence, in addition to contributing to antimicrobial responses, they may carry out autoreactively activated functions when there is no infectious challenge. However, the immunological consequences of NKT cell autoreactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 39 publications
5
59
1
3
Order By: Relevance
“…We have recently shown that GM-CSF and IL-13 secretion by autoreactive NKT cells induces human monocytes to differentiate into immature DCs. 36 Hence, we speculate that the particular pattern of cytokine production resulting from NKT-cell autoreactive activation, comprising mainly GM-CSF and IL-13, may serve to constitutively promote monocyte differentiation into DCs. The identities of the auto-antigens recognized by human NKT cells remain unknown; thus, their TCR affinity is not clear.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We have recently shown that GM-CSF and IL-13 secretion by autoreactive NKT cells induces human monocytes to differentiate into immature DCs. 36 Hence, we speculate that the particular pattern of cytokine production resulting from NKT-cell autoreactive activation, comprising mainly GM-CSF and IL-13, may serve to constitutively promote monocyte differentiation into DCs. The identities of the auto-antigens recognized by human NKT cells remain unknown; thus, their TCR affinity is not clear.…”
Section: Discussionmentioning
confidence: 92%
“…34 DCs were prepared by short-term culture of fresh human peripheral blood monocytes with granulocyte macrophage colony-stimulating factor (GM-CSF) and IL-4 as described. 36 CD1d transfectants were generated from the 3023 human lymphoblastoid cell line as described. 37 Studies were approved by the University of Wisconsin Minimal Risk Institutional Review Board, and written informed consent was obtained from all blood donors in accordance with the Declaration of Helsinki.…”
Section: Nkt Cells and Apcsmentioning
confidence: 99%
“…Previous studies have shown that NK, CD8 Ï© and NK T cells can also initiate DC differentiation. 31,45,46 Similar to T H cells, NK cells colocalize with monocytes in inflamed tissue and direct DC differentiation in a GM-CSF and cell contact dependent manner. 46 Comparison of the relative contributions of each of these cell types to inflammatory responses merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that human-activated NKT cells direct monocytes to differentiate into immature DCs (31) and that cytokines produced by the NKT cells, including IL-13 and GM-CSF, could induce differentiation in monocytes. In the current study, we found that the levels of CD11c and CD86 on MDSCs were increased by activated NKT cell-mediated stimulation in naive mice.…”
Section: Discussionmentioning
confidence: 99%